From Research Participants to Video Stars: Engaging Families in End-of-Grant Knowledge Translation. (November 2018) - Ollivier, Rachel; Aston, Megan; Price, Sheri
This article aims to describe an innovative, arts-based approach to knowledge translation (KT) by involving study participants and families in end-of-grant KT. Examples of end-of-grant KT are scarce in the literature and there is a need to better involve families and participants in various stages of health research, including dissemination. Inclusion of families in research needs to extend beyond serving as participants and on advisory boards. Inclusion of families in end-of-grant KT initiatives can provide a very rewarding experience in which they are able to contribute to enhancing the care experience for others. Our unique KT approach, titled "Mindful Matters, " provides an example of how families may be given "first voice" in creating real and relatable KT materials, such as a video.